2021
DOI: 10.1002/adhm.202101215
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D Titanium Carbide MXene (Ti3C2Tx) Nanoflakes Activate WNT/HIF‐1α‐Mediated Metabolism Reprogramming for Periodontal Regeneration

Abstract: Periodontal defect regeneration in severe periodontitis relies on the differentiation and proliferation of periodontal ligament cells (PDLCs).Recently, an emerging 2D nanomaterial, MXene (Ti 3 C 2 T x ), has gained more and more attention due to the extensive antibacterial and anticancer activity, while its potential biomedical application on tissue regeneration remains unclear. Through a combination of experimental and multiscale simulation schemes, Ti 3 C 2 T x has exhibited satisfactory biocompatibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 101 publications
1
39
1
Order By: Relevance
“…In summary, the excellent bone repairing ability of the 0.4%MXene/RSF + ES group may be ascribed to two factors: (i) MXene is degraded to release Ti-based species since the exposure to water and oxygen, which may promote osteogenesis and neovascularization. Cui et al demonstrated that MXene have highly efficient therapeutic effects for osteogenic differentiation by activating the WNT/HIF-1α-mediated metabolism reprogramming [ 60 ]. Meanwhile, it was also reported that Ti-molecules couple with osteogenesis and angiogenesis processes by upmodulating the PI3K/AKT signaling pathway [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the excellent bone repairing ability of the 0.4%MXene/RSF + ES group may be ascribed to two factors: (i) MXene is degraded to release Ti-based species since the exposure to water and oxygen, which may promote osteogenesis and neovascularization. Cui et al demonstrated that MXene have highly efficient therapeutic effects for osteogenic differentiation by activating the WNT/HIF-1α-mediated metabolism reprogramming [ 60 ]. Meanwhile, it was also reported that Ti-molecules couple with osteogenesis and angiogenesis processes by upmodulating the PI3K/AKT signaling pathway [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Cui et al have demonstrated that Ti 3 C 2 T x MXene induces distinguish differentiation of human periodontal ligament cells by activating WNT/HIF1-𝛼 signaling pathway. [26] Through GO enrichment analysis on mRNA-seq data, we find cell response to interferon-𝛽 in top 10 GO terms has been significantly up-regulated. Interferon-𝛽 activity has been reported to be regulated by mTOR signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Others stated that MXene concentrations are safe up to 180 μg mL −1 for human periodontal ligament cells and safety up to 500 μg mL −1 for HaCat cell line in 2D culture system. [26,45] Furthermore, Ti 3 C 2 Tx is a potential material for tissue restoration following tumor surgery due to its great selectivity against tumor cells compared to normal cells. [46] In addition, MXenes have an outstanding electrical conductivity of ≈15 100 S cm−1 for a 214 nm thick film, [22] making it promising to adjust the conductivity of Matrigel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations